INFLUENCE OF BRAND LOYALTY AND BRAND EQUITY THROUGH SOCIAL MEDIA MARKETING ON BUYING INTENTION TOWARDS ELECTRONIC HOME APPLIANCES (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
To grab the consumer base, marketers are  devising strategies to integrate their advertising  and marketing campaigns across multiple  channels. Among these channels of marketing,  social media continues to be the most preferred  marketing tool. The objective of this paper  is to study the impact of social media on  consumer buying decisions, considering  brand equity and brand loyalty in relation to  electronic home appliances. In the present  study, 497 respondents are collected through  self-structured questionnaires. A model has  been developed and tested using structural  equation modeling. Thus, the study makes a  significant contribution that will be helpful  for marketers to improve the quality of their  products and attain maximum consumer  satisfaction. It is found that brand equity and  brand loyalty have both direct and indirect  impact through social media marketing on  consumer buying intentions.
Keywords: Social media marketing; buying intention; brand loyalty